Study on Engraving Resistance Characteristic of Band Based on Different Structure Parameters of Rifling. Issue 4 (May 2020) - Liu, Qi; Wang, Yuwei; Li, Ruijing; Zhu, Wenfang; Zhao, Na
Abstract: The gun barrel working in complex environments is prone to damage, including the wear and ablation of the bore in the gun barrel. These changes cause changes in the rifling structure, which in turn affects the combustion law of gunpowder gas, which affects the pressure in the bore and changes the internal ballistics of the gun performance. This article takes a large caliber howitzer as the research object, considers the frictional force change during high-speed and high-pressure sliding, and also considers the energy conservation criterion during the engraving process. The initial ballistic equations are established during the initial movement period and Coupled solution with band engraving process. Considering the large deformation, high strain rate, temperature softening effect and cumulative damage effect, an explicit dynamic algorithm is used to compare the differences of the elastic band engraving process under different rifling structure parameters. The influence of different rifling structure parameters on the force state of the belt is analyzed. The influence of the main structural parameters of the engraving system on the belt engraving process is obtained. It provides a useful reference for the integrated analysis of the ammunition and the gun and the optimization of the barrel structure.